(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Optimization of gastric resection in bariatric surgery requires an integrative evaluation of clinical, anatomical, functional, and pathomorphological characteristics of the stomach. Modern bariatric approaches increasingly emphasize not only the restrictive component of sleeve gastrectomy but also its metabolic and hormonal impacts, which depend on the microstructure of gastric mucosa, endocrine cell distribution, vascular architecture, and muscular morphology. This article provides a comprehensive analysis of the clinical and pathomorphological foundations that determine optimal resection boundaries, including the extent of fundic excision, antral preservation, stapling trajectory, and prevention of postoperative functional stenosis. Particular attention is given to endocrine factors (e.g., ghrelin secretion zones), mechanisms of gastroesophageal reflux exacerbation, and structural variations influencing postoperative outcomes. Based on evidence from recent clinical and morphologic research, key recommendations are formulated for individualized surgical planning. The article highlights how a pathomorphology-guided, patient-specific resection strategy can enhance weight-loss sustainability, reduce complications, and improve long-term metabolic results.